Accession is, above All, about Benefits - Jacques Pelkmans (Romanian Journal of European Affairs, 2004)
Accession is about prosperity and, in this context, all candidate countries should be confident in their opportunities in the process of becoming full members of the European Union. It is crucial that decision makers of such countries dispose of profound and analytically respectable ‘impact studies’ on horizontal and sectoral subjects. Such studies should aim to clarify analytically what the acquis implies for sectors or broader themes and attempt to build models or scenarios helping to understand the nature and magnitude of short term and longer term effects of adjusting to the acquis or indeed exploiting its opportunities to the full.